Correctness and accuracy of bootstrap confidence intervals - Linda, Bohdan; Kubanová, Jana (Univerzita Pardubice, 2003)
This paper describes some theoretical backgrounds of confidence interval construction. The order of accuracy that reach the bounds of the confidence interval determined by a standard normal method, bootstrap t-method and BCa method is analyzed in a detail way.
Keywords: statistické metody; intervalový odhad; spolehlivost